A novel hybrid compound LLP2A-Ale both prevented and rescued the osteoporotic phenotype in a mouse model of glucocorticoid-induced osteoporosis - Mohan, Geetha (Calcif Tissue Int, 2016)
Prolonged glucocorticoid (GC) administration causes secondary osteoporosis (GIOP) and non-traumatic osteonecrosis. LLP2A-Ale is a novel bone seeking compound that recruits mesenchymal stem cells to the bone surface, stimulates bone formation, and increases bone mass. The purpose of this study was to determine if treatment with LLP2A-Ale alone or in combination with parathyroid hormone (PTH) could prevent or treat GIOP in a mouse model. Four month old male Swiss-Webster mice were randomized to a prevention study with placebo, GC (day 1 – 28), and GC + LLP2A-Ale (IV, day 1) or a treatment study with placebo, GC (day 1 – 56), GC + LLP2A-Ale (IV, day 28), GC + PTH, and GC + LLP2A-Ale + PTH (day 28 – 56). Mice were sacrificed on day 28 (prevention study) or on day 56 (treatment study). The study endpoints included bone mass, bone strength, serum markers of bone turnover (P1NP and CTX-I) and angiogenesis (VEGF-A), surface-based bone turnover, and blood vessel density. LLP2A-Ale prevented GC-induced bone loss and increased mechanical strength in the vertebral body (day 28 and 56) and femur (day 56). LLP2A-Ale, PTH, and LLP2A-Ale + PTH treatment significantly increased the mineralizing surface, bone formation rate, mineral apposition rate, double labeled surface and serum P1NP level on day 56. LLP2A-Ale and PTH treatment increased femoral blood vessel density and LLP2A-Ale increased serum VEGF-A on day 28. Therefore, LLP2A-Ale monotherapy could be a potential option to both prevent and treat GC-induced osteoporosis and bone fragility.